IMPLEMENTATION OF THE COMMUNICATION POLICY OF THE ORGANIZATION OF GOVERNMENT IN INDONESIA - Nawi, Rusdin (Journal of Humanity, 2015)
The research aim to know the application policy of organization communication which applied by government in Indonesia. These research applied on Government in Indonesia. The informant namely have relevant with task to give policy which must applied related with the policy of organization communication. Data analysis which collected it as well as primary and secondary data and further to arrange, to analysis, to interpretation then take of conclusion as the answe of problem. The result of research showed that organization communication have communicated by head of instance and job unit and subordinate it in application of main task and function in aim to task by Governor. The application of organization communication it created of organization climate which conducive in vertically, horizontal and diagonal by leader of job unit and subordinate in organization to applied of policy, main task and function which obligate it.Â